Economic Optimizer for Building Energy Rating - Chavez-Orostica, H; Fuentes-Parra, C; Riquelme-Vera, E (Institute of Electrical and Electronics Engineers Inc., 2024)
The construction sector is responsible for emitting 30% of worldwide greenhouse emissions. Sustainable construction addresses this problem by designing infrastructures under the energy-efficient concept. This paper presents an energyefficient optimal methodology for designing the thermal envelope and energy support technologies of the infrastructure, according to the energy qualification established in 21.305 law. The methodology consists of carrying out a mathematical formulation of the optimization problem for an energy solution implementing a Home Energy Rating (CEV) as an input parameter, which allows obtaining specific results for all the elements that participate in the property s requirement. Specifically, simulations were carried out of a house located in the north and south of Chile considering different parameters such as floor, walls, windows, etc. Simulating in each area and restricting the energy rating where the sensitivity of the problem to the different parameters is observed. Finally it is possible to conclude about the minimum energy requirements. © 2024 IEEE.